Seeing is believing: believing in a just world reduces perceived inequality - John, Melvin; Bless, Herbert (Frontiers in Psychology, 2025)
IntroductionInequality is one of the most pressing social issues of our time, yet individuals often differ in how they perceive and evaluate it. These subjective differences hinder the formation of a common understanding, making it difficult to reach consensus on how to address inequality. This research investigates the role of fairness beliefs-specifically just world beliefs (BJW) and meritocracy-in shaping individual perceptions of inequality.MethodsWe conducted three studies across four independent samples (Ns between 543 and 36,281), using experimental, survey, and cross-national designs. Study 1 experimentally manipulated fairness beliefs. Study 2 analyzed two representative German samples. Study 3 employed multilevel modeling with data from 40 countries.ResultsFairness beliefs, particularly belief in a just world (BJW), consistently influenced both the perceived and evaluated size of financial inequality across all three studies. Experimental evidence (Study 1) showed a causal effect of BJW on both these components. In large-scale observational data (Studies 2 and 3), BJW remained a significant predictor of perceived and evaluated inequality across diverse national samples.DiscussionThese findings suggest that BJW not only influences how people evaluate inequality but also shapes their perception of its scale. By identifying fairness beliefs as a core factor behind subjective inequality, this work provides insights into the psychological roots of disagreement about inequality and offers a foundation for addressing these divides in public discourse and policy.